Developments in research on monitoring training loads in athletes: bibliometric analysis - Muhamad Fahmi Hasan; Tommy Apriantono; Bagus Winata; Trisha Aryanti Septina; Gifran Rihla Gifarka Latief; Yudhi Teguh Pambudi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Monitoring training load can help improve performance, predict injury risk, determine athlete readiness, and keep track of health conditions. By using bibliometric analysis methods, one can evaluate publications from institutions or countries and track the growth or decline of a specific field. The purpose of this study is to compile a bibliography of works on the subject of training load monitoring that were published between 1979 and 2023. This study analyzes publications on training load monitoring and uses scientific mapping to describe the structure and trends. Contributions from countries, authors, cited articles, frequently appearing keywords, and keyword trends are all covered in this study. According to the findings, research was scarce during the first two decades and significantly increased in the next. While Australia has the most publications, the European continent dominates this research field. Most articles are published in and referenced from the International Journal of Sports Physiology and Performance. Furthermore, due to its high citation count, Halson's article had the greatest influence. Some keywords are related and appear in this study. This article presents a trend visualization that academics can use as a reference guide.